Treatment of Granulomatous Mastitis with Half-Yin and Half-Yang Syndrome - Li, Zhikun; Cheng, Xufeng; Zhang, Wenke; Zhao, Huiduo (Chinese medicine and natural products, 2023)
Granulomatous mastitis (GM) is a refractory chronic mastitis, which belongs to the category of “acne mammary abscess” and “ulcer” in Traditional Chinese External Medicine. According to yin-yang syndrome differentiation, the disease can be divided into yin syndrome, yang syndrome, and half-yin and half-yang syndrome. Among them, the theories and treatment of yin syndrome and yang syndrome are relatively comprehensive in Traditional Chinese External Medicine. However, the half-yin and half-yang syndrome lacks a specific theoretical elaboration and treatment system, which is a special and complex syndrome of the disease, limiting the improvement of the clinical efficacy of the disease. The core pathogenesis of GM with half-yin and half-yang syndrome is “obstruction of nutritive and defensive phases, and yin-yang obstruction.” The clinical features are local yin syndrome complicated with yang syndrome, and the disease is lingering and difficult to cure. For syndrome differentiation, it is advisable to “attach more importance to the local while less importance to the whole body.” The treatment should be based on the general principle of “eliminating yin and transforming yang.” For the use of herbs, it is recommended to adopt the methods of “the combination of the herbs in cold and warm nature, mainly with herbs in warm nature, attaching more importance to use the herbs with the function of ascending and less to descending.” Finally, restore the normal circulation of qi and blood as well as the balance of yin and yang to achieve the purpose of treatment.
Keywords: granulomatous mastitis; acne mammary abscess; half-yin and half-yang syndrome; eliminating yin to transform yang; Chonghe Plaster; Huoluo Xiaoling Bolus; Neituo Shengji Powder